The Lure of Fascism in Western Europe - Orlow, D. author. aut Link
XIV, 260 p.
Keywords: This book breaks new ground by analyzing the reciprocal relationship between a fascism that had reached the power phase (Nazi Germany) and fascist movements in two neighbouring countries which were attempting to come to power in their respective societies.